Can the Iberian Finisterra Terrane extends until Central Europe Variscides? - Moreira, Noel (2018)
The Finisterra Terrane is located in the western sector of the Iberian Variscides and its eastern boundary is a N-S to NNW-SSE lithospheric structure, the Porto-Tomar-Ferreira do Alentejo Shear Zone (PTFSZ). The PTFSZ makes the contact between the Finisterra Terrane and two distinct paleogeographic zones of the Iberian Terrane: Central Iberian and Ossa-Morena Zones.